Effects of captopril in acute and chronic heart failure. Correlations with plasma levels of noradrenaline, renin, and aldosterone. Issue 1 (January 1983) - Wenting, G J; Man in't veld, A J; Woittiez, A J; Boomsma, F; Laird-Meeter, K; Simoons, M L; Hugenholtz, P G; Schalekamp, M A
Abstract : The angiotensin-converting enzyme inhibitor, captopril, was given to 19 patients with severe heart failure. Seven patients had acute myocardial infarction and the remainder had chronic myocardial damage caused by ischaemia or valvular disease. Cardiac filling pressures were raised in all, the pulmonary capillary "wedge" pressure being 17 mmHg or more. Captopril, 50 mg orally, raised stroke volume and cardiac output, and reduced heart rate, cardiac filling pressures, systemic arterial pressure, and the plasma concentrations of aldosterone and noradrenaline. These changes were attended by clinical improvement. Decrements in cardiac filling pressures, systemic arterial pressure, and total peripheral resistance were positively correlated with pretreatment plasma renin. Long-term treatment with captopril was offered to 14 patients. Four patients with severe coronary disease died suddenly after initial clinical improvement. In nine patients haemodynamic measurements were repeated after three months. The results showed sustained effects on cardiac output and filling pressures but there was no loss of body weight. The haemodynamic effects were at least as good as with previous vasodilators. The fall in systemic arterial pressure, however, was greater with captopril. Captopril may become a valuable adjunct to the treatment of acute and chronic heart failure, but more information about its effect on coronary blood flow is required.